Till as natural isolating cover and its sedimentation in glacial environment - Baltrūnas, Valentinas; Šinkūnas, Petras; Karmaza, Bronislavas; Dundulis, Kastytis; Česnulevičius, Algimantas; Kazakauskas, Vaidotas; Šeirienė, Vaida; Kukytė, Daiva; Januševičiūtė, Eglė (2008)
The aim of this research carried out was to study the features of till as a natural isolating cover and its sedimentation in present glacial environments. For this task the results of earlier research in Lithuania of till structure, clast-fabric analysis and physical properties were systematized and analyzed. The features of till sedimentation were preliminary studied at the margin of Russell Glacier in southwestern Greenland. Variety of sedimentation conditions of glacial and glacially related deposits determined that the identification of different till types of old (Pleistocene) continental glaciations require a methodology prepared on the results of research in sedimentation environments of modem glaciers. The preliminary study results of elastic material in basal ice at the margin of Russell Glacier in comparison with the same data from area (Lithuania) of old continental glaciation enable to make some insight into sedimentation and postsedimentation processes of tills as a natural isolating cover.